Pengaruh Pembiayaan UMKM Terhadap Peningkatan PDB Sektor Pertanian Pada Masa Pandemi Covid-19: Studi Empiris pada Sektor Pertanian dalam SEKI dan SSKI Bank Indonesia Periode 2020-2021 - Riyanto, Cipto; Pusparani, Indi; Hardianti, Mia; Sari, Novita; Dahmhudi, Dudi (Koaliansi : Cooperative Journal, 2022)
Despite the economic slowdown, the agricultural sector grew during the Covid-19 pandemic. The growth of the agricultural sector equates to the growth of the capital needs of agricultural MSMEs. The purpose of this study is to analyze the impact of MSMEs financing in the agricultural sector on the GDP growth of the agricultural sector during the Covid-19 pandemic. This study uses a simple linear regression method, with agricultural MSMEs financing as the independent variable and GDP growth in the agricultural sector as the dependent variable. The data used in this study are 2020-2021 MSMEs Credit Data for Agriculture, Hunting, and Forestry Sector and 2020-2021 Gross Domestic Product at Current Market Prices by Industry (Agriculture, Forestry, and Fishery) which is processed into annual GDP growth year on year (yoy) data. The results show that the financing of MSMEs in the agricultural sector had a 45,6% significant impact on GDP growth in the agricultural sector while 54,4% is influenced by other factors that are not investigated in this study.